Extension of energy band gap in ternary photonic crystal using left-handed materials. (August 2018) - El-Amassi, Dena M.; Taya, Sofyan A.; Ramanujam, Nambi R.; Vigneswaran, Dhasarathan; Udaiyakumar, R.
Abstract: We investigate the extension of energy band gap in one-dimensional ternary photonic crystal. We assume one of the layers constituting the ternary photonic crystal to be left-handed material (LHM) of simultaneously negative electric permittivity and magnetic permeability. The photonic crystal has the structure dielectric/LHM/dielectric. We show in this work, the energy band gap in one-dimensional ternary photonic crystal can be dramatically enlarged with the increase of the LHM layer thickness. Moreover, it can also be enlarged with the decrease of both the negative permittivity and permeability of the LHM layer. The effects of the angle of incidence and the number of layers are also investigated. Highlights: The extension of band gap in ternary photonic crystal is investigated. One of the layers is assumed to left-handed material (LHM). Band gap can be dramatically enlarged with the increase of the LHM layer thickness. It can also be enlarged with the decrease of both ε and μ of the LHM layer.